1982
DOI: 10.1002/pssa.2210730208
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Twin Microstructure on the Magnetic Properties of Alloys with CuAul Superlattice Ordering

Abstract: The special features of a microstructure of type CoPt alloys are examined. A model of a ferromagnetic crystal with twin microstructure is suggested. The distribution of the magnetization vectors in the twin crystal is obtained. The effect of twin‐oriented domain thickness and of the magnetic field on this distribution is determined. A model of the magnetic domain structure of a stack of twin plates is proposed, taking into account known magnetic domain observation results. The connection between the magnetic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
1

Year Published

1991
1991
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Crystal defects, which have been observed in the bulk and thin L1 0 -FePt film, are mainly plane defects, such as twin and antiphase domain boundary. [25][26][27][28][29][30] It has been suggested that these defects are associated with magnetic hardness of the L1 0 -FePt. [28][29][30] In the bulk L1 0 -FePt, the twin structure has been determined to be the {110} type, i.e., the twinning plane is {110}.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Crystal defects, which have been observed in the bulk and thin L1 0 -FePt film, are mainly plane defects, such as twin and antiphase domain boundary. [25][26][27][28][29][30] It has been suggested that these defects are associated with magnetic hardness of the L1 0 -FePt. [28][29][30] In the bulk L1 0 -FePt, the twin structure has been determined to be the {110} type, i.e., the twinning plane is {110}.…”
mentioning
confidence: 99%
“…[28][29][30] In the bulk L1 0 -FePt, the twin structure has been determined to be the {110} type, i.e., the twinning plane is {110}. 25,28 The {111} type twin was observed in FePt film. 29,30 We have presented a detailed high-resolution microscopic study on phase transformation, coalescence, and twin microstructure of thermally annealed monodisperse 6 nm Ft 52 Pt 48 nanocrystals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…В [15,16] рассмотрены неелевские стенки двух типов и Доменные стенки характеризуются тем, что в центре двойниковой границы магнитный момент направлен вдоль нормали к плоскости границы. Магнитостатическая энергия, связанная с образованием такой стенки, мала, и ее вкладом в общую энергию можно пренебречь [20,35]. В этом приближении поверхностная плотность энергии неелевской стенки равна Следовательно, что оправдывает существование стенок Нееля на двойниковых границах.…”
Section: 1unclassified